2016
DOI: 10.1038/srep31720
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Ideal Cardiovascular Health Metrics and Extracranial Carotid Artery Stenosis in a Northern Chinese Population: A Cross-Sectional Study

Abstract: Past epidemiologic studies have indicated that the ideal cardiovascular health (CVH) metrics are associated with a lower risk of cardiovascular diseases (CVDs) and stroke. Carotid artery stenosis (CAS) causes approximately 10% of ischemic strokes. The association between ideal CVH and extracranial CAS has not yet been assessed. In the current study, extracranial CAS was assessed by carotid duplex ultrasonography. Logistic regression was used to analyze the association between ideal CVH metrics and extracranial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…6 Our previous study based on the Jidong community indicated that the participants in the highest ideal CVH metrics summary score quartile had a 71% decreased prevalence of extracranial carotid artery stenosis (CAS) compared to those in the lowest summary score quartile. 9 In addition, the ankle brachial index and brachial-ankle pulse wave velocity were also demonstrated to be risk factors for CVH. 10,11 Maintaining an ideal status of CVH risk factors with a focus on preventing the occurrence of risk factors is crucial for the prevention of CVDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Our previous study based on the Jidong community indicated that the participants in the highest ideal CVH metrics summary score quartile had a 71% decreased prevalence of extracranial carotid artery stenosis (CAS) compared to those in the lowest summary score quartile. 9 In addition, the ankle brachial index and brachial-ankle pulse wave velocity were also demonstrated to be risk factors for CVH. 10,11 Maintaining an ideal status of CVH risk factors with a focus on preventing the occurrence of risk factors is crucial for the prevention of CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…The risks of atherosclerotic plaque or coronary artery calcium were each reduced by approximately 60% in subjects with 6 or 7 ideal factors compared to 0 to 2 ideal factors in a prospective cohort study . Our previous study based on the Jidong community indicated that the participants in the highest ideal CVH metrics summary score quartile had a 71% decreased prevalence of extracranial carotid artery stenosis (CAS) compared to those in the lowest summary score quartile . In addition, the ankle brachial index and brachial‐ankle pulse wave velocity were also demonstrated to be risk factors for CVH .…”
Section: Introductionmentioning
confidence: 99%
“…A validated questionnaire specifically designed for this study was used to collect clinical data from all participants by trained doctors 50 . Demographic information (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Hypertension was defined as presence of at least one of the following status: 1) history of arterial hypertension; 2) using antihypertensive medication; or 3) a SBP >140 mmHg or a DBP >90 mmHg. The body mass index (BMI) was calculated as body weight (kg) divided by the square of the height (m 2 ), after measuring body weight (kg) and height (cm) on the day of tests 50 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation